Status of vitamin D and disease pattern among sedentary adults 18-60 years attending a selected institution in Dhaka city - Islam, Mohammad Shahidul; Ali, M. Younus; Shil, Ripon Chandra; Ranzu Ahmed, M. (International Journal of Research in Medical Sciences, 2023)
Background: Vitamin D deficiency is a global health concern affecting individuals across all the age groups in both the genders. It is an essential element that is essential for the production, regulation and absorption of calcium and phosphorus by the human body, as well as for the proper maintenance of teeth and bones and to make your immune system work. Vitamin D is not actually a vitamin; it falls under the pro-hormone category. Because the human body is perfectly capable of producing vitamin D on its own when exposed to sunlight, and vitamins are the type of nutrients that the body cannot or cannot produce automatically, that we consume through dietary supplements. Methods: It was a cross sectional study the sample size was 369. Vitamin D level of all the participants was estimated by using an ADVIA Centaur XPT stem designed to perform continuous operations immunoassay methods. The data were processed to undergo statistical analysis using SPSS 23 windows program. Microsoft Word, Microsoft Excel were used to represent the tabular, charts and graphical icon. Results: The prevalence of vitamin D deficiency exhibited a medical condition increment in both the males and females. This study had clear association was observed using bivariate analysis for any of the three chronic conditions such as hypertension, cardiovascular disease and osteomalacia where (p=0.021), (p=0.039) and (p=0.000) explored in the current study with severe deficiency status. Conclusions: Vitamin D deficiency was prevalent even in apparently healthy young individuals; this study is suggestive of a higher prevalence of vitamin D deficiency among young adults, females, Bangladeshi nationality and those with higher BMI.